Impact Of Storage On Quality Parameters Of Meat Analog Nuggets Formulated From Oyster Mushroom, Flaxseed And Amaranth (Applied Biological Research, 2019)
The present study was envisaged to formulate meat analog nuggets from  Oyster mushroom, flaxseed and amaranth and characterize its quality and  shelf stability under ambient conditions. The water absorption index, fat  absorption index, water activity and total microbial count of meat analog  nuggets were analyzed for six months at two months interval. The mean  water activity, oil absorption index and microbial count of meat analog  nuggets increased from 0.558 to 0.604, 2.60 to 2.75 g g-1 and 0.172 × 104to  2.863 × 104cfu g-1, respectively, during six months storage. However, the water absorption index of meat analog nuggets decreased from 5.06 to 4.03  g g-1 during six months storage. The study revealed higher values of water  and oil absorption index in meat analog nuggets formulated from higher  levels of freeze-dried Oyster mushroom; while the incorporation of defatted  flaxseed decreased water activity of meat analog nuggets. The microbial  load of meat analog nuggets was within the permissible limits of BIS (4 × 104 cfu mL-1) throughout storage period of six months.
Keywords: Meat analog; microbial load; mushroom; oil absorption index; water absorption index; water activity